History of Cardiovascular Disease, Intensive Lifestyle Intervention, and Cardiovascular Outcomes in the Look AHEAD Trial. Issue 2 (3rd January 2020) - ; Lewis, Cora E.; Bantle, John P.; Bertoni, Alain G.; Blackburn, George; Brancati, Frederick L.; Bray, George A.; Cheskin, Lawrence J.; Curtis, Jeffrey M.; Egan, Caitlin; Evans, Mary; Foreyt, John P.; et al.
Abstract : Objective: To examine the effects of an intensive lifestyle intervention (ILI) on cardiovascular disease (CVD), the Action for Health in Diabetes (Look AHEAD) trial randomized 5, 145 participants with type 2 diabetes and overweight/obesity to a ILI or diabetes support and education. Although the primary outcome did not differ between the groups, there was suggestive evidence of heterogeneity for prespecified baseline CVD history subgroups (interaction P = 0.063). Event rates were higher in the ILI group among those with a CVD history (hazard ratio 1.13 [95% CI: 0.90‐1.41]) and lower among those without CVD (hazard ratio 0.86 [95% CI: 0.72‐1.02]). Methods: This study conducted post hoc analyses of the rates of the primary composite outcome and components, adjudicated cardiovascular death, nonfatal myocardial infarction (MI), stroke, and hospitalization for angina, as well as three secondary composite cardiovascular outcomes. Results: Interaction P values for the primary and two secondary composites were similar (0.060‐0.064). Of components, the interaction was significant for nonfatal MI ( P = 0.035). This interaction was not due to confounding by baseline variables, different intervention responses for weight loss and physical fitness, or hypoglycemic events. In those with a CVD history, statin use was high and similar by group. In those without a CVD history, low‐density lipoprotein cholesterol levels were higher ( P = 0.003) and statin use was lower ( P ≤ 0.001) in the ILI group. Conclusions: Intervention response heterogeneity was significant for nonfatal MI. Response heterogeneity may need consideration in a CVD‐outcome trial design.